STANDARDS APPLIED IN PROTECTION OF TAXPAYERS’ RIGHTS - Klonowska, Alina (Scientific Journal of Bielsko-Biala School of Finance and Law, 2016)
The paper discusses selected legal solutions, from Polish tax system, which are to protect taxpayer’s rights. Using judgments issued by institutions adjudicating in tax cases, biding tax law provisions were critically assessed, in particular, the principle of trust. Consequently, based on the experience of selected countries, the weaknesses of legal solutions in force in Poland were mentioned, including difficult access to the information about the taxpayer's rights, lack of the Charter of Taxpayer’s Rights as well as limiting the need for trust only in relation to tax proceedings.